2023
DOI: 10.1021/acsami.3c00612
|View full text |Cite
|
Sign up to set email alerts
|

SERS Nanowire Chip and Machine Learning-Enabled Classification of Wild-Type and Antibiotic-Resistant Bacteria at Species and Strain Levels

Abstract: Antimicrobial resistance (AMR) is a major health threat worldwide and the culture-based bacterial detection methods are slow. Surface-enhanced Raman spectroscopy (SERS) can be used to identify target analytes in real time with sensitivity down to the single-molecule level, providing a promising solution for the culture-free bacterial detection. We report the fabrication of SERS substrates having tightly packed silver (Ag) nanoparticles loaded onto long silicon nanowires (Si NWs) grown by the metal-assisted che… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…coli and V. parahemolyticus, which was primarily explained by the fact that peptidoglycan thickness in Gram-positive bacteria was higher (10–20 layers) than that in Gram-negative bacteria (1–3 layers). , Compared to the degree of signal at 731 cm –1 , E. coli and V.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…coli and V. parahemolyticus, which was primarily explained by the fact that peptidoglycan thickness in Gram-positive bacteria was higher (10–20 layers) than that in Gram-negative bacteria (1–3 layers). , Compared to the degree of signal at 731 cm –1 , E. coli and V.…”
Section: Resultsmentioning
confidence: 98%
“…33 Particularly, the signal level of S. aureus at 731 cm −1 was substantially greater than E. coli and V. parahemolyticus, which was primarily explained by the fact that peptidoglycan thickness in Gram-positive bacteria was higher (10−20 layers) than that in Gram-negative bacteria (1−3 layers). 9,34 Compared to the degree of signal at 731 cm −1 , E. coli and V. parahemolyticus have a more significant signal at 662 cm −1 than S. aureus, which is possibly related to the signal of bacterial outer membrane proteins perceived only in Gram-negative bacteria. 35 These differences revealed that the prepared paperbased microarray SERS chips have a promising capability of distinguishing between various types of pathogenic bacteria.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18–21 Sathi et al reported a SERS substrate with tightly packed silver (Ag) nanoparticles on silicon nanowires (Si NWs) to detect AMR strains and Escherichia coli , with 10 2 CFU mL −1 detection limits. 22 Wang et al reported polyethyleneimine-modified Au-coated magnetic microspheres and Au@Ag and concentrated Au@Ag nanoparticles (NPs). They detected Escherichia coli and Staphylococcus aureus , demonstrating a detection limit as low as 10 3 CFU mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Existing SERS platforms primarily probe the bacterial cell wall. This approach has its limitations because it can be overly ideal and can only be derived in controlled, isolated laboratory conditions, thus not accurately representing bacteria in their natural habitats. In their natural habitats, bacteria are often encapsulated by a complex extracellular matrix (ECM) comprising exopolysaccharides, proteins, and DNA. This matrix forms around and between individual cells in response to its native environment.…”
mentioning
confidence: 99%